Expand -(3 - c)(c + 2(3 - c) - 7(c - 5)) .What is the sum of the coefficients of the expanded form?

Guest May 17, 2022

#1**0 **

If you have a polynomial, substitute 1 into the polynomial and that will be the sum of the coefficients.

Therefore, sum of coefficients = -(3 - 1)(1 + 2(3 - 1) - 7(1 - 5)) = -66.

To check the answer, we can go the normal way and see if we really get this sum of coefficients.

-(3 - c)(c + 2(3 - c) - 7(c - 5))

= (c - 3)(c + (6 - 2c) - (7c - 35))

= (c - 3)(c + 6 - 2c - 7c + 35)

= (c - 3)(-8c + 41)

= -8c^2 + 24c + 41c - 123

= -8c^2 + 65c - 123

sum of coefficients = -8 + 65 - 123 = **-66**.

Therefore the answer is correct.

MaxWong May 18, 2022